Analisis Pengakuan Pendapatan, Belanja, dan Pembiayaan Daerah Pada Pemerintah Daerah Kota Bogor - Pratiwi, Yuri; Pamungkas, Bambang (Institut Bisnis dan Informatika Kesatuan, 2014)
Recognition of Revenue, Expenditure, and Financing Area applied by the Bogor City Government is using cash basis toward accrual and the cash basis for the recognition and measurement of revenue, expenditure, and financing as well as the accrual basis for the recognition and measurement of assets, liabilities, and equity. Policies, recording, and accounting report for revenue, expenditure, and financing areas that applied by the Bogor City Government is in conformity with PSAP No. 02 by PP No. 24 of 2005 about Government Accounting Standards. Where for the recognition of revenue, expenditure, and financing areas, recognition using the cash basis. While the measurement of income, expenditure, and financing of used area using the currency. While the revenue, expenditure, and financing areas measured in foreign currency must be converted into rupiah at Bank Indonesia middle rate on the transaction date. Accounting records for revenue, expenditure, and financing areas that applied by the Bogor City Government is fully in accordance with the PSAP No. 02 by PP No. 24 of 2005. Where records for revenue, expenditure, and financing area, the recording using the cash basis